The Implementation and Use of ERMS: A Study in Icelandic Organizations - Jóhanna Gunnlaugsdóttir 1949- (2006)
Doktorsritgerð varin við Háskólann í Tampere, Finnlandi This research studied the implementation and use of ERMS in eight organizations in Iceland. Four organizations, where 34 employees were interviewed, were studied in detail. Seven participant observations were also conducted in these organizations. Four other organizations, where four key employees were interviewed, corroborated the findings. Six consultants/teachers at six different software providers were also interviewed, making the total number of interviewees 44. One participant observation was conducted as well at one of the software providers. These eight organizations operated in different fields of industry. They had implemented four different ERMS with two using each system. The organizations were both public and private. They are representative of medium to large size organizations in Iceland and had experienced varying success rates in the implementation, although detailed results were not known before this study. ERMS are systems to manage records during their lifetime. The systems studied met all RM requirements. They were all part of a groupware and were those that had gained the widest distribution on the Icelandic market. The aim of the research was to discover why and how ERMS were being implemented and to find out whether and how employees were actually using ERMS. The study aimed at examining the association between the implementation and the use of ERMS. The focus was to discover which implementation factors influenced a successful outcome and the actual use as well as the perceived objectives of the implementation. The study discovered that there was a strong correlation between the most important input factors and the outcomes that they influence. There were mainly three implementation factors that appeared to be most important for the success of the implementation. These were support by top management, co-operation between the IT and RM functions in the system development and in the training, and the training of the users who should ...